1996
DOI: 10.1128/jb.178.5.1248-1257.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the caiF gene encoding a potential transcriptional activator of carnitine metabolism in Escherichia coli

Abstract: Expression of the Escherichia coli caiTABCDE and fixABCX operons involved in carnitine metabolism is induced by both carnitine and anaerobiosis. When cloned into a multicopy plasmid, the 3 region adjacent to the caiTABCDE operon was found to increase levels of carnitine dehydratase activity synthesized from the chromosomal caiB gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 35 publications
3
65
0
2
Order By: Relevance
“…Besides autoregulation, it has been noticed in many cases (Dickson et al 1975;Eichler et al 1996;Palacios and Escalante-Semerena 2000;Torres et al 2003) that TFs and the genes they regulate are near each other in the genome. Both phenomena imply a distance constraint between the TF and its closest binding site in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Besides autoregulation, it has been noticed in many cases (Dickson et al 1975;Eichler et al 1996;Palacios and Escalante-Semerena 2000;Torres et al 2003) that TFs and the genes they regulate are near each other in the genome. Both phenomena imply a distance constraint between the TF and its closest binding site in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of binding in vitro may be the result of different situations, including the possibility that GrlA may become inactive upon purification or that it requires another factor for DNA binding. Correlating with the second possibility, it has been shown that CaiF, the only characterized homologue of GrlA, binds more efficiently to the intergenic cai-fix regulatory region when CRP is present (3) and also counteracts H-NS repression (15). Furthermore, IHF has been shown to be essential for ler expression in EPEC (19) and for pCRler-cat fusion expression in E. coli K-12 (unpublished results), making it a candidate for acting synergistically with GrlA to activate ler expression.…”
Section: Discussionmentioning
confidence: 99%
“…The closest GrlA homologue is the putative product of an uncharacterized gene found in different Salmonella enterica serotypes. In addition, GrlA is 23% identical to CaiF, a regulatory protein responsible for the carnitine-dependent induction of the cai and fix E. coli operons under anaerobic conditions and the best-characterized member of this novel family of transcriptional regulators (15). A motif search of GrlA has also revealed the presence of a putative helix-turn-helix DNA binding motif at its N-terminal domain, where most of the similarity with CaiF and the Salmonella GrlA homologue (Sgh) is found (12).…”
mentioning
confidence: 99%
“…In addition, it has been proposed that a positively controlled caiF gene, 3V adjacent region to the cai operon, acts as a specific transcriptional regulator for carnitine metabolism (Eichler et al, 1996). This pathway is detectable not only in cells previously grown anaerobically but also in some species, such as E. coli ATCC 25922 and DSM 8828, P. vulgaris, and P. mirabilis, grown under aerobiosis in the presence of inducers such as D,L (-)-carnitine mixture or crotonobetaine (Cánovas et al, 2002;Elssner et al, 2000;Kleber, 1997;Obón et al, 1999).…”
Section: E Coli Carnitine Metabolismmentioning
confidence: 99%
“…Genetic studies have been conducted to elucidate carnitine metabolism in E. coli O44 K74 (Kleber, 1997). Two divergent structural operons, caiTABCDE and fixABCX, are coexpressed, the former being responsible for the enzymes of carnitine metabolism and the latter being required to provide electrons for carnitine reduction (Eichler et al, 1996;Walt and Kahn, 2002). Although the pathway/genome database of E. coli is available (Karp et al, 2002), if the cell biochemistry and physiology to optimize this bioprocess is to be understood, it will be necessary to decipher the links, quantify the kinetics, and determine the regulatory structure of the metabolic pathways involved in the different scenarios, such as the reactor type used and the cell either in the growing or resting state.…”
Section: Introductionmentioning
confidence: 99%